2018
DOI: 10.1001/jamasurg.2018.3174
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Prediction Model for Mortality and Adverse Outcomes Among Patients With Peripheral Eosinopenia on Admission for Clostridium difficile Infection

Abstract: This study describes a simple, widely available, inexpensive model predicting CDI severity and mortality to identify at-risk patients at the time of admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 24 publications
3
67
2
1
Order By: Relevance
“…While C. difficile toxins drive epithelial disruption and disease during CDI, recently, many groups have demonstrated that the type of host immune response generated against C. difficile also dictates the severity of symptoms during infection, independent of bacterial factors [26][27][28][29][30]. The host immune system has a multifaceted role during CDI with some level of inflammation required to clear the infection.…”
Section: Microbiota-elicited Immunity and Its Importance In Combatingmentioning
confidence: 99%
“…While C. difficile toxins drive epithelial disruption and disease during CDI, recently, many groups have demonstrated that the type of host immune response generated against C. difficile also dictates the severity of symptoms during infection, independent of bacterial factors [26][27][28][29][30]. The host immune system has a multifaceted role during CDI with some level of inflammation required to clear the infection.…”
Section: Microbiota-elicited Immunity and Its Importance In Combatingmentioning
confidence: 99%
“…While we detected robust eosinophil infiltration in the cecum of young mice, we did not observe this in the colon of young or aged animals. Another group found that peripheral loss of eosinophils in patients with C. difficile infection was predictive of severe disease (4). We report that young mice had significantly increased numbers of intestinal eosinophils during C. difficile infection, compared to mock-infected young controls, while aged mice did not have intestinal eosinophil infiltration and significantly worse CDI disease, compared to young mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, peripheral eosinophil counts were found to be predictive of CDI disease severity and mortality in patients (4), and eosinophils were shown to potentially be protective in mouse models of CDI (5, 6). Eosinophils are innate immune cells that predominantly reside in close proximity to microbes that colonize mucosal surfaces under non-inflammatory homeostasis (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Kulaylat et al developed a model based on findings translated from a mouse model. 2 They hypothesized that admission eosinopenia, defined as a peripheral eosinophil level of 0 k/µl, is associated with worsened outcomes. Using both a training and a validation cohort, they determined that eosinopenia is an independent predictor of inpatient mortality (OR 2.01, 95% CI 1.08–3.73).…”
mentioning
confidence: 99%